FAKTOR-FAKTOR YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PETANI DALAM PENERAPAN PERTANIAN PADI ORGANIK DI DESA SUKOREJO KECAMATAN SAMBIREJO KABUPATEN SRAGEN - Lisana Widi Susanti; Sugihardjo Sugihardjo; Suwarto Suwarto (AGRITEXTS: Journal of Agricultural Extension, 2008)
This thesis is written based on the research conducted with an aim at studying the farmers' decision making in reaction to the application of organic rice farming, the factors influencing the farmers· decision making, and the significance of the factors towards the decision making in the application of organic rice farming in Sukorejo Village, Sambirejo District, Sragen Regency. The basic method of this research is descriptive which is applied with survey technique. The research was conducted in Sragen Regency. Purposively, Sambirejo district was chosen with a reason that it has the widest area of organic rice planting in Sragen Regency in the second planting season of the year 2007. From this sample, Sukorejo Village was then taken since it is the village which 01-vns the widest organic rice planting area in the second planting season of the year 200 7. In this research, 60 respondents taken were those who have the experience of planting organic rice. Respondents were taken with the use of simple random sampling method. The result of the research shows that the farmers ' decision making towards the application of organic rice planting in Sukorejo Village, Sambirejo District, Sragen Regency, in the initiation stage, was included into high category. Meanwhile, in the persuasion stage, it was categorized into moderate category, in the decision-making stage it was in the high category, and in the confirmatiolj stage it was categorized into moderate catego,y. The factors influencing farmers· decision in the application of organic rice planting are: age, education, the extent ofthe farming system, income level, economic environrr,ent, social environment, and innovation character. The relationship between age, the extent of the farming system, income level, innovation character and the farmers· decision is insignificant. The relationship between education and social environment and the farmers' decision is very-significant. Meanwhile, the relationship between economic environment and the farmers· decision is significant.